Metal hydroxide catalyst for water splitting - Neo, Yu Chen (Nanyang Technological University, 2021)
With the drive towards a hydrogen economy and environment sustainability, the need for an effective yet affordable electrocatalyst for an oxygen evolution reaction (OER) in water splitting becomes more prevalent than ever. In this report, we investigate and synthesize an ideal metal hydroxide comprising of an ideal stoichiometric ratio of cobalt and manganese components in order to give an enhanced OER performance. In order to study the effects of Mn substitution in Co, the ratio of Co and Mn in our synthesis of CoxMn3-x(OH)6, is variedwhere x= 3.0, 2.5, 2.0, 1.5, 1.0, 0.5 and 0. To assess the OER performance of the catalyst, we performed X-ray Diffraction (XRD), Scanning Electron Microscopy with Energy Dispersive X-Ray Analysis (SEM-EDX), Cyclic Voltammetry (CV), Linear Sweep Voltammetry (LSV), Potentio Electrochemical Impedance Spectroscopy (PEIS) measurement and stability tests. Based on our findings, Co2.5Mn0.5 is the optimal OER catalyst in terms of its OER activity and durability. Its high OER activity is from surface modifications of Co atoms due to Mn doping, resulting in Co’s presence as a dominant phase. This result demonstrates the potential that further studies can be done in order to produce an efficient non-noble catalyst for OER.